THE INFLUENCE OF REALISTIC MATHEMATICS EDUCATION (RME) ON STUDENT PROBLEM-SOLVING IN BASIC STATISTICS - Ayu Sardono, Anisah Zahra; Fauzia, Zahra; Indriyani , Rini; Wahyunengsih (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
To enhance students' comprehension of mathematical problem solving, particularly when learning Basic Statistics, this project intends to apply the methodology of Realistic Mathematics Education (RME). This research was conducted quantitatively, with data collected through posttest and pre-test-based experiments. The study results stated that students taught using the RME method showed stronger critical thinking abilities than students taught with the conventional method. In particular, students taught using the RME method showed a discernible grade rise. Based on the questionnaire responses, 80% of students stated that learning by linking mathematics to real life makes learning more effective and enjoyable. As a result, the combined posttest and pretest tests demonstrated here demonstrate the RME approach's beneficial effects. This supports the finding that RME enhances students' comprehension and addresses problems by relating math ideas with real scenarios.